Unleashing compassionate care: canine-assisted intervention as a promising harm reduction approach to prisonization in Canada and its relevance to forensic psychiatry - Gibson, Maryellen; Dell, Colleen Anne; Chalmers, Darlene; Rath, Grace; Mela, Mansfield (Frontiers in Psychiatry, 2023)
In recent years, there has been a global advancement in the offering of canine-assisted interventions (CAI) in prisons. However, these programs have focused primarily on the benefits to the dogs involved and not the impacts on the participantrisoners. The authors of this perspective paper have been running a CAI program with therapy dogs, called PAWSitive Support, in a Canadian federal prison since 2016. Thoughts from the program facilitators and interviews with prison staff indicate that the program, and specifically the therapy dogs, provide a unique and integrated source of comfort, support, and love for participants. These benefits are consistent with those seen in CAI programs outside of prisons. Unique to the prison setting appears to be an improvement in participantrisoner-staff relations. The therapy dogs have helped participants to experience comfort and consequently express their emotions. This seems to contribute to their recognition of support within the prison system, and specifically developing trust with staff. Additionally, the dogs have helped to create an experience of feeling love within the prison, interpreted as feeling cared for, which is rare for this populationprisoners. The authors suggest that the integration of a therapy dog intervention in prison could be a novel harm reduction strategy to address issues related to prisonization and associated mental health concerns, including substance use. This consideration can offer unique insight to the field of forensic psychiatry about providing compassionate care to patientsrisoners.